Factors causing low back pain in undergraduate medical students; A cross-sectional study - Muhammad Sohail Anjum Noor; Uzma Kausar; Amir Ahmad; Muhammad Usama Sohail (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Low back pain is a serious health issue among medical students, particularly due to the taxing, rigorous nature of the course curriculum. The study aims to explore the causes and factors responsible for the ailment, with a focus on preventing low back pain, to provide valuable professional input by medical graduates in the future.METHODOLOGY: A cross-sectional study was conducted among the undergraduate students of ABWA Medical College, Faisalabad, Pakistan, from March 2024 to Aug 2024 using a probability sampling technique (simple random). A self-administered questionnaire was distributed to explore the factors responsible for low back pain among undergraduate medical students. The data was collected and analyzed in SPSS 26 using the chi-square test.RESULT: Of 240 participants, 154 (77%) reported low back pain. Prolonged sitting (>3 hours), lack of exercise, stressful conditions, and the hectic routines of medical students were identified as potential causes of low back pain among medical students, with P values of 0.03, 0.008, and 0.008, respectively. The stressful conditions, with increased study hours and long lecture hours, have been shown to be statistically significant (p-value < 0.05).CONCLUSION: The prevalence of low back pain has increased to an alarming extent. Students should adopt a healthy lifestyle to cope with the stressful life in medical college.